CHALLENGES AND DILEMMATIC CONDITION OF HUMAN RESOURCE MANAGEMENT DURING THE FOURTH INDUSTRIAL REVOLUTION (4IR) - Sri Wijaya Tasa Gome; Tiarapuspa (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2023)
Economic growth necessitates a circular economy in which production and productivity must be improved quickly. One of the major needs of economic management is efficiency throughout the process, one of which is the employment of fewer employees who are replaced by IT and advanced machinery. The purpose of this work is to present the problems and dilemmatic state of that situation by acquiring information and data from current reviews and research articles published in scientific publications. According to this viewpoint, the large population, particularly those of productive age, may be projected as prospective primary participants in the economic sector. These can be accomplished through the development of IT skills. This issue necessitates government attention and a vital role in which human skill vision may be improved via education and training. The demographic dividend can be tailored to boost economic growth in the coming years. Furthermore, initiative, innovation, and entrepreneurship must be essential human resource skills.